Wykorzystanie map wiedzy w realizacji koncepcji wywiadu gospodarczego - Kwieciński, Mirosław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The conception of maps of knowledge is to meet the need to lessen the lack of knowledge. This is of consequence in competitive intelligence. The maps of knowledge are perceived as tools of purposive location of resources of knowledge. In the conception of competitive intelligence it is possible to mark out the following maps of knowledge: maps of inspiration in searching knowledge, maps of ways of search knowledge, maps of accumulation knowledge, maps of processing knowledge, maps of users of knowledge, maps of technology of knowledge protection. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1086, s. 150-159